2009
DOI: 10.1038/sj.bjc.6605281
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, tobacco and domestic fumes intake are associated with nasopharyngeal carcinoma in North Africa

Abstract: Cigarette smoking and snuff (tobacco powder with additives) intake were significantly associated with differentiated NPC but not with undifferentiated carcinoma (UCNT), which is the major histological type of NPC in these populations. As demonstrated by a stratified permutation test and by conditional logistic regression, marijuana smoking significantly elevated NPC risk independently of cigarette smoking, suggesting dissimilar carcinogenic mechanisms between cannabis and tobacco. Domestic cooking fumes intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 24 publications
2
87
0
1
Order By: Relevance
“…Table 3). ( 11,12,27 ) .The pooled odds ratios for the association of waterpipe tobacco smoking with esophageal cancer was OR= 4.14 (95% CI= 0.93, 18.46). The level of statistical heterogeneity was high (I 2 =96%).…”
Section: -Esophageal Cancermentioning
confidence: 93%
“…Table 3). ( 11,12,27 ) .The pooled odds ratios for the association of waterpipe tobacco smoking with esophageal cancer was OR= 4.14 (95% CI= 0.93, 18.46). The level of statistical heterogeneity was high (I 2 =96%).…”
Section: -Esophageal Cancermentioning
confidence: 93%
“…In North African countries, such as Tunisia-AlgeriaMorocco, case-witness studies, suggested that salted foods prolonged consumption, like quaddid (dried mutton stored in oil), harissa (spicy salted sauce, rancid butter and khelii (dried meat, salty, spicy, cooked and preserved in a mixture of oil and melted bovine greases) is associated with increased NPC risk (Feng et al, 2007) Other environmental factors such as tobacco, cannabis and domestic cooking fumes intake (cooking in the main living room) during childhood, have recently been described as a risk factors for NPC in North African countries as in Tunisia (Feng et al, 2009). We're always observing in North Tunisia a bimodal distribution characterized by 2 peaks at 15 -20 years old and a second at 50 years old, previously reported in several intermediate-risk populations in Northern Africa (Tabyaoui et al, 2013) and Western Asia (Andejani et al, 2004;Barista et al, 2007;Tsao et al, 2014;).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, as a non-viral personal factor, was significantly associated with a 2 to 3 fold higher incidence of NPC than non-smoking in a dose-dependent manner [5][6][7][8][9].…”
mentioning
confidence: 96%